Seasonal dynamics and optimization of tapping methods for sustainable gum harvest in tropical forests of Western Odisha, India - Paramanik, Tapas; Deep, Pratibha; Bhattacharyya, Shantanu (Ethnobotany Research and Applications, 2025)
Background: Natural gums are among the most economically significant Non-Timber Forest Products (NTFPs) in India, mostly used as food, fodder, and medicine. In Western Odisha, gum extraction is a key income source for tribal communities. Unsustainable tapping practices severely reduce gum yield and adversely affects tree health. Thus, a sustainable harvesting method is essential for ecological and economic balance. Methods: We studied twelve gum-producing tree species over three years in Western Odisha. We tested gum yields in different wound types such as size (from 5x5cm to 15x15cm), shape (rectangle, V shape and. Circle hole), location (bottom, middle, or upper trunk), direction (north, south, etc.), and timing (pre-monsoon to winter). Results: Sterculia urens showed highest gum yielding potential. The most effective method was a 10x10cm2 rectangular cut on the middle of the trunk, facing east-west, during summer (April-June). This produced 35% more gum than other methods and allowed trees to recover wound. Circular cuts healed 20% slower than rectangular ones. Monsoon tapping reduced yield quality by 40% due to rain wash and moisture contamination, while in winter it reduces by ~55%. Conclusions: Our findings provide a standardized method for sustainable gum harvesting in terms of wound size, shape, position, directions along with seasonal dynamics. Rectangular wounds (10×10cm², mid-trunk, east-west) during summer are optimized condition for sustainable gum yield and tree health. These findings can guide government or NGOs to train Odisha’s gum collectors, fostering a sustainable circular economy that boosts rural incomes, secures NTFP-based livelihoods, and safeguards forest health. Keywords: Non-timber forest products (NTFPs), Sterculia urens, Seasonal gum production, Climate-resilient Forest management, Gum tapping, Gum exudation optimization, Forestry resource management, Sustainable forestry,